The function of the indicative, structural, evaluative, and characteristic criteria in the analysis of the generative process of meaning and signification in linguistic and literary indicative systems - Mehyar Alavi Moghaddam (مطالعات زبانی و بلاغی)
Semiotics is a new field of study in explaining the function of the underlying layers of the signs, achieving the mutual relations between the signs, and its accomplishment is to discover how meanings emerge. Accordingly, we need a framework in the field of semiotics to enable us to understand the process of meaning emergence. In spite of the distinction between the "designation of meaning" based on Saussure's semiotic theory and the "lack of designation of meaning," based on the belief in the dark layers and the mystery of the text, it seems according to structuralism, semiotic theories of Saussure and post-structuralism can achieve an understanding of the literary text and the process of meaning emergence and criteria in the linguistic structures and literary signs of the text and difference between word level to meaning in linguistic work and sign to meaning in literary work. Four criteria: indicative, structural, evaluative, and characteristic can help to analyze the generative process of meaning and interpretation of the literary text. Hence, the aim of this research is the achievement of the foundations of the semiotics base on the four categories of "indication", "structure", "character" and "value", and four indicative, structural, evaluative, and characteristic criteria. Among these linguistic studies and semiotic, the distinction between the significance of the "word" on meaning in lingual work and the significance of "sign" on meaning in "literary work," and the two signal linguistic and literary systems are important. Ali Mohammad Haghshenas recounted these four categories and criteria.